HUBUNGAN AKTIVITAS OLAHRAGA PADA LANSIA HIPERTENSI DENGAN TINGKAT HIPERTENSI - Derry Mertianda; Reni Zulfitri; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Sports activity is one form of intervention in an effort to prevent diseases that experienced by the elderly one of which is hypertension. This study aims to determine the relationship between exercise activity in the elderly with hypertension and the level of hypertension in the working area of the Kemalaraja Health Center, Baturaja, South Sumatra. This research is a quantitative research that uses a descriptive descriptive research design. The sample of this study was 73 elderly people who were taken based on inclusion criteria by using purposive sampling technique. The instruments used in this study were a questionnaire, a sphygmomanometer, and a stethoscope. The statistical tests used in this study were the chi-square test and the man whitney test. There were 43 elderly respondents (58.9%) which showed that sports activities carried out by the elderly were optimal. The statistical test results obtained showed that there was a significant relationship between exercise activity in hypertensive elderly and hypertension level with p value (0.001)> alpha (0.05). There is a significant relationship between exercise activity in hypertensive elderly with hypertension level. Keywords: Connection, Elderly, Hypertension, Hypertension Levels, Sports Activities